2022
DOI: 10.3390/molecules27207090
|View full text |Cite
|
Sign up to set email alerts
|

Honey-Propolis-Engineered Collagen Peptides as Promising Wound-Healing Matrix in Mouse Model

Abstract: In this study, collagen hydrolysates (CHDs) were fabricated with honey-propolis wax (HPW), structurally modified as a sponge matrix, and experimentalized on wound healing in a mouse model. The scaffold was characterized by means of in vitro enzymatic degradation; in vitro HPW release; and in vivo wound-healing mouse model, wound-healing-specific RNA, transcripts, and protein markers. The functional activity of the HPW extracted from raw propolis was determined using total flavonoids, antioxidant scavenging ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…1 produce honey with excellent nutritional and medicinal value with potent antimicrobial action 5,6 and enhance wound healing by reducing the level of inflammation, edema, and pain through suppression the activities of cyclooxygenases 1 and 2 (COX1 and COX2). 7 Correct treatment of chronic wounds and ulcers is a complex process, which requires de-trauma, drainage and anti-inflammatory therapies, 8 so honey is a favorable as it promotes tissue repair 9 re-epithelization, 10 collagen deposition, 2 debridement action, 11 plays a role in tissue regeneration since honey-induced extracellular Ca2+ entry results in wound healing, which is consistent with the role played by Ca2+ signaling in tissue regeneration. 12 Rather than it has durable adhesive characteristics for skin graft fixation.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…1 produce honey with excellent nutritional and medicinal value with potent antimicrobial action 5,6 and enhance wound healing by reducing the level of inflammation, edema, and pain through suppression the activities of cyclooxygenases 1 and 2 (COX1 and COX2). 7 Correct treatment of chronic wounds and ulcers is a complex process, which requires de-trauma, drainage and anti-inflammatory therapies, 8 so honey is a favorable as it promotes tissue repair 9 re-epithelization, 10 collagen deposition, 2 debridement action, 11 plays a role in tissue regeneration since honey-induced extracellular Ca2+ entry results in wound healing, which is consistent with the role played by Ca2+ signaling in tissue regeneration. 12 Rather than it has durable adhesive characteristics for skin graft fixation.…”
Section: Introductionmentioning
confidence: 76%
“…The biological activities of propolis involved in wound healing and tissue regeneration correlates with its antimicrobial, anti-inflammatory and immunomodulatory properties. 74 The antimicrobial synergistic action of both honey and propolis is recommended in vitro 5,75 and in vivo 10 since their combination stimulates the monocytes/macrophages to release cytokines important for wound healing, and promote neutrophils 54 rather than B-lymphocytes (antibody production) 67 protecting the healing tissue from pathogenic infection. 54 A study 76 concluded that honey supplemented with propolis extract can be an excellent source of antioxidant compounds as significant increase in the content of polyphenolic compounds, including flavonoids and phenolic acids, of which chrysin, pinocembrin, p-coumaric acid, and ferulic acid were present in the highest amounts.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations